Pemberdayaan Kader Posyandu Dalam Mengelola Sampah Berbasis Masyarakat Jalur Tol Soker di Desa Wonorejo Kab.Karanganyar - triyono, kharis; Sumarmi, Sumarmi; Indriastuti, Dorothea Ririn (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Community Partnership Program (PKM) activity partners are people who are not economically productive (general/ordinary community) Posyandu Cadre Ibu Sadar 2 is located in Wonorejo Village, Gondangrejo District, Karanganyar Regency, which is located. In RW I Wonorejo, there are problems with the large amount of garbage scattered around the settlements due to the unavailability of waste collection and processing facilities, many sick children who have to go to the hospital due to the lack of cleanliness in environmental conditions, therefore it is necessary to empower posyandu cadres in managing community-based waste. The objectives of this community partnership program (PKM) are: 1) improving the skills, knowledge and attitudes of partners in treating waste, 2) motivating partners to always be creative and innovative in managing waste through the 3 R's (Reduce, Reuse, Recycle), 3) encouraging partners improving and maintaining waste management in the environment so that a healthy, comfortable, peaceful and prosperous atmosphere is obtained and 4) for universities as a form of implementing MBKM based on the second and third Main Performance Indicators (IKU), namely students and lecturers active outside campus. The methods to be used in achieving the above objectives are outreach to community leaders and partners, imparting knowledge and skills through lectures, field practice, discussions, and assistance in making useful items from waste and planting fruits and vegetables in pots. The output targets of this community partnership program are: 1) Posyandu cadres as partners can become pioneers in community-based waste management 2) are able to make goods from waste that have economic value, 3) have the skills and knowledge to make organic fertilizer from the waste used to meet their needs in growing fruits and vegetables in pots, and 4) publication through a national journal with ISSN in the Adi Widya Journal with ISSN 2598-2273 (print media) and ISSN 2598-2281 (online media) which have been indexed by Sinta and mass media online as well as YouTube